The metabolic effects of fatal cyanide poisoning. Issue 770 (December 1989) - Singh, B. M.; Coles, N.; Lewis, P.; Braithwaite, R. A.; Nattrass, M.; FitzGerald, M. G.
Abstract : Metabolic and toxicological data were obtained during the first 24 hours following severe and eventually fatal cyanide poisoning. Initial blood cyanide concentrations were 804 mumol/l but fell rapidly over 24 hours following cobalt edetate therapy to 15 mumol/l. However, plasma thiocyanate concentrations rose over 24 hours (147-267 mumol/l) suggesting continued tissue detoxification. The major metabolic abnormality was lactic acidosis (initial pH 7.21, blood lactate 17.5 mmol/l) which corrected over 12 hours. Despite high circulating insulin concentrations the responses of blood glucose, plasma non-esterified fatty acid, blood glycerol and 3-hydroxybutyrate suggested marked insulin resistance.